Respostas estratégicas das empresas do setor financeiro da B3 à crise da Covid-19 e seu impacto no desempenho econômico-financeiro sob a perspectiva da teoria da contingência - Voltz, Juliana Poerschke (Universidade do Vale do Rio dos Sinos, 2022)
This research has as its theme the strategic responses of Brazilian companies to the crisis in the dimensions of containment, perseverance, innovation and exit. The objective of the research is to identify the strategic responses of companies in the financial sector on B3 (Brasil, Bolsa, Balcão) to the COVID-19 crisis from a contingency perspective and what impacts they had on their economic and financial performance. The research is relevant because it highlights the responses of Brazilian companies that emerged from the crisis situation and can contribute to facing future crises and studies on management control. The research is based on: Contingency Theory; strategy concept; strategic response to the crisis; other studies related to economic-financial indicators. The research is descriptive, uses document analysis and content analysis. The survey results are: the combination of strategic responses is the most frequent response to the COVID-19 crisis by financial sector companies on B3; there is a significant difference between companies in the financial sector on B3 that combine strategic responses and those that do not; there is a correlation between the combination of strategic responses of financial sector companies in the B3 to the crisis; there are some relationships between the strategic response of financial sector companies listed on B3 and their economic-financial performance in 2021.
Keywords: Empresas brasileiras; Setor financeiro; Respostas estratégicas; Crise; COVID-19; Brazilian companies; Financial sector; Strategic answers; Crisis; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis